Einflüsse räumlicher Strukturen auf den Industrialisierungsprozeß in Kolumbien - Brücher, Wolfgang (ERDKUNDE, 1977)
According to an opinion widely held in Columbia, the country’s limited degree of industrialisation is largely due to its relief, which has led to its being split up into sub regions as well as to an extraordinary dispersion of its urban population and industrial capacity. However, this dispersion has been decisively re-inforced by anthropogenic process (agrarian structure, infrastructural opening-up, state industrialisation policies). Whilst it has until now retarded industrial development, this polycentric structure, together with increasing modernisation of the infrastructure, today on the contrary offers more favourable conditions by far for regionally-balanced economic growth than in other monocentrically moulded countries in South America. The government’s economic policy of centralisation, however, runs contrary to such an advantageous development.